Application of Gross Tissue Response System in Gastric Cancer After Neoadjuvant Chemotherapy: A Primary Report of a Prospective Cohort Study - Yang, Hua; Zhang, Wei-Han; Ge, Rui; Peng, Bo-Qiang; Chen, Xin-Zu; Yang, Kun; Liu, Kai; Chen, Xiao-Long; He, Du; Liu, Jian-Ping; Zhang, Wei-Wei; Qin, Yun; et al. (Frontiers in Oncology, 2021)
Objective We previously established a gross tissue response (GTR) system to evaluate the intraoperative response of perigastric tissue in patients with gastric cancers to neoadjuvant chemotherapy. This prospective cohort study aims to confirm the relationship between gross tissue response and clinicopathological characteristics and explore the possibility of using the GTR system to predict the difficulty of surgery and the occurrence of postoperative complications within 30 days. Methods A total of 102 patients with gastric cancer from January 2019 to April 2020 were enrolled in this study. The degrees of fibrosis, edema, and effusion in the perigastric tissues were assessed intraoperatively according to the GTR system. We systematically analyzed the relations between GTR and clinicopathological characteristics, and then a prediction model that includes GTR was established to predict the difficulty of surgery and the occurrence of postoperative complications within 30 days. Results Finally, the study included 71 male patients and 31 female patients. The patients had an average age of 58.79 ± 1.03 years, BMI of 22.89 ± 0.29, and tumor diameter of 4.50 ± 0.27 cm. Among these patients, 17 underwent laparoscopic gastrectomy, 85 underwent open gastrectomy, the average operation time was 294.63 ± 4.84 minutes, and the mean volume of intraoperative blood loss was 94.65 ± 5.30 ml. The overall 30-day postoperative complication rate was 19.6% (20/102). The total GTR was significantly related to the primary tumor stage, operation time and 30-day postoperative complication rate (p<0.05). Edema and effusion were significantly related to intraoperative blood loss (p<0.05). The logistic regression analysis identified that the total GTR score (score: 4-9, OR 2.888, 95% CI: 1.035-8.062, p = 0.043) was an independent risk factor for postoperative complications within 30 days, and the total GTR score (score 4-9, OR 3.32, 95% CI 1.219-9.045, p=0.019) was also an independent risk factor for operation time. The AUC of the total GTR score for predicting postoperative complications within 30 days was 0.681. Conclusion According to the results of the present study, the gross tissue response (GTR) system is an effective tool that may be used to predict the risk of a difficult operation after neoadjuvant chemotherapy and postoperative complications. Although neoadjuvant chemotherapy improves the therapeutic effect, it also increases the risk of surgical trauma and postoperative complications. Clinical Trial Registration ClinicalTrials.gov, identifier NCT03791268.